« Ne formez pas avec les infidèles d’attelage disparate ». L’enjeu matrimonial dans les diasporas des xvie-xviiie siècles - Natalia Muchnik (Diasporas: Circulations, Migrations, Histoire)
This paper focuses on the marriage practices of religious minorities scattered in Early Modern Europe (Huguenots, Sephardic Jews, Jacobites, etc.). In particular, it shows that marriage is at the diasporic level a way to link the different community settlements among themselves and with the land of origin, and also provides a form of socio-cultural cohesion. Locally, the choice of spouse is of course crucial to the maintenance of the group and in terms of acculturation and assimilation. Marriage is thus a touchstone of diasporic identity, between autonomy and integration.